Abhandlung vom See-Protest - Meyersieck, Gotthard Heinrich (bey Karl Christoph Stiller, 1804)
Fraktūras burti.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law; Jūras tiesības; Jūras apdrošināšana; Maritime law; Marine insurance; Seerecht